Hemocoagulation Conditions Associated with Venom-Induced Consumption Coagulopathy due to Snakebite in Humans - Prasetiyanti, Rinta; Hernaningsih, Yetti (Folia Medica Indonesiana, 2024)
Highlights: 1. This review comprehensively highlighted aspects of hematologic abnormalities in snakebites, a topic that remains understudied globally. 2. This review contributes insights into the field of snakebite research and improves the management of snakebites by examining the diverse effects of different types of snakebites on hemocoagulation status. Abstract Snakebite remains an underreported health hazard worldwide. The most common effects of snakebite envenomation globally are hematological disorders, with venom-induced consumption coagulopathy (VICC) being the most prevalent and significant condition. This review aimed to explore the hematological aspects of snakebite, with a focus on snakebite-induced consumption coagulopathy. We conducted a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines through a search across several databases, namely PubMed, ScienceDirect, and Google Scholar. The inclusion criteria for this review were studies on snakebite envenomation in humans with a discussion of relevant cases. Additionally, the included studies were conducted between 2010 and 2023 and published in the English language. Studies on animal models were excluded. We used the keywords “venom-induced consumption coagulopathy AND snake" in the search. The critical appraisal was performed using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Case Reports and the Mixed Methods Appraisal Tool (MMAT). The findings were presented as a qualitative synthesis of 14 articles covering 316 patients and various snakebite types. The studies on snakebite came from various countries, but mostly from Sri Lanka. The snake types exhibited variation, with certain species existing only in specific areas. The subjects fell into different age groups, from children to the elderly. The majority of the subjects were male. The subjects' youngest age was 6 years old, while the oldest was 70 years old. Prothrombin time (PT) and activated partial thromboplastin time (APTT) were the most discussed variables. Some of the studies demonstrated an increase in PT and APTT, although other studies reported contrasting findings. In conclusion, certain types of snakebite have a different impact on the hemocoagulation status.